Accuracy of improved zero heat flux core temperature monitoring in non-cardiac surgery for patients undergoing general anesthesia - Yan Liang; Jing-yan Wang; Xin-feng Shao; Ze-guang Wang; Mei-na Gao; Hao Liang (Scientific Reports)
Abstract Due to various factors such as anesthesia, the core body temperature of perioperative patients often fluctuates significantly. Ideal core temperature measurements are particularly needed during the perioperative period for early identification of hypothermia and malignant hyperthermia, and even to guide intraoperative temperature protection. This study aimed to evaluate the consistency of the optimized Zero-Heat-Flux (ZHF) thermometer with esophageal temperature monitoring under general anesthesia. Adult patients, classified as American Society of Anesthesiologists (ASA) I–III, who are scheduled for elective surgery will be enrolled in this study. Both esophageal and ZHF core temperature monitoring were measured simultaneously. The consistency and correlation between the two measurements were evaluated using Bland–Altman analysis, linear regression methods, and the percentage of differences within ± 0.5 °C. The sensitivity and specificity of the ZHF temperature in identifying hypothermia were further validated. Ninety patients with a total of 1035 pairs of measurements were analyzed. Bland–Altman analysis revealed a mean difference between ZHF temperature and esophageal temperature of 0.06 ± 0.26 °C, with 95% limits of agreement ranging from − 0.57 to 0.46 °C. 96.0% of the measurement differences were within ± 0.5 °C. The consistency correlation coefficient was 0.89 (95% CI 0.88–0.90). The sensitivity and specificity of ZHF temperature monitoring in diagnosing hypothermia were 0.86 and 0.91 respectively. The modified ZHF core temperature monitoring system demonstrates good accuracy and consistency with esophageal temperature monitoring during general anesthesia for surgery. ZHF temperature monitoring is highly reliable for diagnosing hypothermia, though further research is needed to evaluate its accuracy.